PRESERVING CULTURAL MEMORY AND IDENTITY OF EVICTION THROUGH DIGITAL ARCHIVES: A CASE STUDY OF @tamansarimelawan INSTAGRAM ACCOUNT - Al Hakim, Zulfi; Pratama, Himawan; Aviandy, Mochamad (International Review of Humanities Studies, 2026)
This study examines how the Instagram account @tamansarimelawan plays a significant role in preserving collective memory and the identity of marginalized groups through digital archives. In the context of the Taman Sari urban village community, which resisted land eviction for the construction of row houses in Bandung, this research explores how Instagram as a social media platform contributes to the formation and maintenance of collective memory and community identity. Using content analysis of the @tamansarimelawan account, the study investigates the mechanisms through which social media functions as a digital repository, a medium for fostering a sense of belonging and continuity, and as a form of resistance among community members. The study employs Halbwach’s (1992) concept of collective memory to emphasize how collective memory is constructed and maintained within a community. Halbwach (1992) argues that memory is not only an individual phenomenon but also a collective one shaped by social context and interactions. This perspective is highly relevant for understanding how the @tamansarimelawan account documents and preserves the collective memory of eviction events experienced by the Taman Sari community. The account is analyzed through its visual content and narrative construction, including the documentation of photos, videos, and hashtags. These elements are examined to understand how digital archives contribute to the formation of a resistance identity and political awareness among both the community and the account’s followers. The posts shared on the account serve not only as records of events occurring during the eviction period but also as a medium to express grievances, aspirations, and collective solidarity among residents. The digital archiving conducted by @tamansarimelawan serves a dual function: it facilitates a voice for resistance and the building of solidarity within the community, while simultaneously documenting and broadcasting eviction events to a broader audience. This demonstrates that social media, through platforms like Instagram, can be a powerful tool for preserving the collective memory and identity of marginalized communities.